Cross-cultural adaptation and validation of the start back screening tool in isiZulu - Schmidt, Peta-Ann (My University, 2019)
Background: Non-specific low back pain (NSLBP) is one of the most prevalent conditions in the world and identifying patients at risk for developing chronic NSLBP is key to effectively treating these patients. The STarT back screening tool is a validated, prognostic screening tool that identifies subgroups of non-specific low back pain patients and the risk factors associated with each subgroup, which can direct the treatment decision-making process in the primary care of NSLBP. This study’s objective was to translate and validate the English version of the STarT back screening tool into isiZulu, making the tool useful and accessible to the isiZulu population of South Africa. Method: Translation was done in four phases, based on best practice guidelines, which included forward translation, synthesis of forward translation, backward translation and expert review. Validation included expert review for content validity and testing and retesting of the preliminary translated tool on a sample of 30 participants. Statistical analysis included content validity, test-retest reliability, usability and internal consistency. Results: Minor linguistic differences occurred with the translating process. The expert committee came to agreement around the challenging translation of the terms “more slowly” in question 4, “physically active” in question 5, “terrible” in question 7 and “bothersome” in question 9. A total of 30 patients were recruited, with 77% female and 23% male. Item content validity for relevance was excellent (I-CVI = 1.00), and satisfactory (I-CVI = 0.94) for clarity, simplicity and ambiguity. Scale content validity was acceptable at 0.955. Spearman’s CC for test-retest reliability was acceptable at 0.73. Cronbach’s Alpha for internal consistency for the total score was 0.68, and the psychosocial scale was also 0.68. Thirty three percent reported the translated tool very easy to understand and 40% reported it very easy to complete. Conclusion: The isiZulu STarT back screening tool showed excellent validity, acceptable reliability, less than acceptable internal consistency and can therefore be used by an isiZulu population of NSLBP patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2019